(untitled) (Journal of Economic Research & Business Administration, 2015)
With the deepening process of globalization and strengthening economic relations in Central Asian region, the scale and fields of cooperation between Kazakhstan and Xinjiang, China are expanding significantly. However, a number of problems occurred in various fields, such as foreign trade, transportation, investment etc. The article pointed out the reasons for these problems on the basis of practical analysis, worked out perspective for further cooperation between the two sides.